Excitation Function for the Production of \(^{96}\)Nb in the \(^{nat}\)Zr(\(p,x\)) Reaction - Do, Nguyen Van; Luan, Nguyen Thanh; Hien, Nguyen Thi; Kim, Guinyun; Thanh, Kim Tien; Khue, Pham Duc; Loat, Bui Van (Communications in Physics, 2021)
We have measured the excitation function for the production of 96Nb in proton induced reaction on natural zirconium in the energy range of 10.58 MeV to 43.61 MeV. The measurement was performed using a stacked-foil activation method combined with off-line γ-ray spectrometry. The stack containing Zr samples, Cu monitors, and several energy degraders was irradiated at the MC-50 Cyclotron of the Korea Institute of Radiological and Medical Sciences (KIRAM), Korea. The cross section of the natZr(p,x)96Nb reaction was extracted from the measured activity of reaction product using an HPGe γ-ray detector. The energy of the proton beam along the stacked foil was calculated using the code SRIM-2013. The proton beam flux was determined via the natCu(p,x)62Zn and natCu(p,x)65Zn monitoring reactions. The measured cross sections of the natZr(p,x)96Nb reaction as a function of the proton energy are compared with the literature data as well as with the theoretical predictions using the TALYS-1.95 nuclear model code and the TENDL-2019 nuclear data library.